DEVELOPMENT OF MODULAR FMCW (FREQUENCY-MODULATED CONTINUOUS WAVE) RADAR SYSTEM - DANIIL KURNIAWAN (NIM : 23216141), HENDRYADI
Frequency-modulated CW is one of the most popular modulation type of CW radar. Its simple and low-cost implementation are some of the reasons that make FMCW radar attractive. FMCW radar has found its application in various fields such as automotive, obstacle penetration, and biomedical application. A modular and flexible FMCW radar system is developed in this thesis. The system is developed so that it can be a learning platform for radar system. The system is divided into three main modules: RF, BBIF, and SPD. RF module uses dechirpon- receiver configuration and operates at S-band (1.8 GHz up to 2.7 GHz). BBIF modules has two microcontrollers as its main components. It implements two approaches for generating chirp, one using DAC and the other using fractional-N PLL. SPD module is a software running in a PC for processing digitized beat signal. Three types of signal processing is implemented, they are range processing, Doppler processing, and SAR image processing. SPD module is also used to configure the system by setting the parameters of the system such as sampling rate, PRF, waveform, bandwitdh, etc. The maximum bandwidth of the generated signal is 900 MHz. Chirp generation with PLL gives a better range resolution than using the DAC approach. The smallest range resolution produced by the system is 0.2 m. A few experiments are done to test the performance of the designed FMCW radar system. These experiments include range measurement, Doppler measurement, and SAR image measurement. The result of range measurement is still affected by the PLL stability problem, while in Doppler measurement, this stability problem does not give much effect on the final result. The usage of RMA on the raw image data in SAR measurement gives a more focused image. The smallest object detected in SAR image has a width of 0.32 m.